The implementation of community based tourism model in the development of the Semambu Island tourism village, Ogan Ilir Regency, South Sumatra - Ulfa Sevia Azni; Alfitri Alfitri (Universitas Trunojoyo Madura, 2020)
This article examines the implementation of CBT model in the development of the Semambu Island Tourism Village. This research uses qualitative research with descriptive research type. Sampling is done by purposive sampling technique, and collecting data is done by in-depth interviews. This study aims to describe the application of CBT (Community Based Tourism) in the management of Semambu Island Tourism Village, the role of various stakeholders, and development in the management and development of Semambu Island Tourism Village in North Indralaya District, Ogan Ilir Regency, South Sumatra. The results showed the concept of CBT applied to achieve tourism planning in this place was applied in the form of local community participation, the establishment of a tourism protection village, management of tourist attraction with an environmental perspective and the creation of community business activities. Management of tourist attractions in the Semambu Island Village emerged from the discovery of local communities. With several considerations concerning the development of Semambu Island Tourism Village, it still needs funding assistance from the local government, providing facilities and infrastructure as a tourist attraction, increasing the number of tourists, and the still limited ideas to add complementary businesses and Semambu Island Tourism Village.